2019
DOI: 10.1002/vms3.158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of egg yolk and soybean lecithin on sperm quality determined by computer‐assisted sperm analysis and confocal laser scanning microscope in chilled canine sperm

Abstract: The reduction of spermatozoa survival time is a major problem of canine chilled sperm for artificial insemination. The aim of the study was to improve the quality of canine chilled sperm during storage time. We therefore, evaluated the effects of eight treatments with different levels of soybean lecithin concentration (1, 3 and 5%) and egg yolk (20%) in Tris‐citric‐fructose or Tris‐citric‐fructose‐mineral salts extender on chilled canine sperm quality during 10 days of storage. The sperm motility was analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
(137 reference statements)
1
15
0
Order By: Relevance
“…Egg yolk-based extender exerts a protective effect on FT semen [ 4 , 32 ]. However, particulates in yolk induce difficulty during semen evaluation and may interfere with FT semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…Egg yolk-based extender exerts a protective effect on FT semen [ 4 , 32 ]. However, particulates in yolk induce difficulty during semen evaluation and may interfere with FT semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, exogenous phospholipids present in EGD and SLD (Khalifa & Abdel‐Hafez, 2014) extenders can supply some of the sperm cells membrane phospholipids to maintain plasma membrane structure and function. The 2nd hypothesis has a widely accepted, it found that phospholipids in either egg yolk or soybean lecithin do not enter the sperm cells membrane to alter the phospholipids membrane concentration but could be formed a protective film around the sperm cells membrane to prevent deterioration of sperm membrane, intracellular fluidity and could protect the sperm cells membrane from mechanical damage during temperature variation (Nguyen, Ponchunchoovong, Kupittayanant, & Kupittayanant, 2019). On the other hand, Mostafa et al., (2018) suggested that the presence of higher calcium ions in egg yolk and lecithin might be concerned with the membrane damage; therefore, it was declared that the normal membrane of spermatozoa has a direct correlation with sperm motility and acrosome status.…”
Section: Discussionmentioning
confidence: 99%
“…It is cleared that EGD, SLD and CPDA lead to significant increase (Nguyen, Ponchunchoovong, Kupittayanant, & Kupittayanant, 2019). On the other hand, Mostafa et al, (2018) suggested that the presence of higher calcium ions in egg yolk and lecithin might be concerned with the membrane damage; therefore, it was declared that the normal membrane of spermatozoa has a direct correlation with sperm motility and acrosome status.…”
Section: Effect Of Egd Sld Cpda and Cpd Extenders On Sperm Characmentioning
confidence: 99%
“…The use of fresh sperm is indicated in male or female that cannot the natural mating for physical or behavioural causes. The storage of sperm (chilled or frozzen) allows a wider genetic improvement of breed advantage of chilled respect to fresh semen are cost relatively inexpensive between countries, animal transportation, and less stressing life-threatening and time-consuming reduces venereal disease risks and allows breeders to use semen from genetically superior dogs, simplify and popularize insemination techniques [1][2].…”
Section: -Introductionmentioning
confidence: 99%
“…Refers to Farelly's Vital Staining subjective assessment 2. Corresponds to normal sperm according to Host-s.Different letters in the same row p <0.001…”
mentioning
confidence: 99%